EULAR points to consider for the development, evaluation and implementation of mobile health applications aiding self-management in people living with rheumatic and musculoskeletal diseases. Issue 2 (13th September 2019) - Najm, Aurélie; Nikiphorou, Elena; Kostine, Marie; Richez, Christophe; Pauling, John D; Finckh, Axel; Ritschl, Valentin; Prior, Yeliz; Balážová, Petra; Stones, Simon; Szekanecz, Zoltan; Iagnocco, Annamaria; et al.
Abstract : Background: Mobile health applications (apps) are available to enable people with rheumatic and musculoskeletal diseases (RMDs) to better self-manage their health. However, guidance on the development and evaluation of such apps is lacking. Objectives: The objective of this EULAR task force was to establish points to consider (PtC) for the development, evaluation and implementation of apps for self-management of RMDs. Methods: A systematic literature review of app content and development strategies was conducted, followed by patient focus group and an online survey. Based on this information and along with task force expert opinion, PtC were formulated in a face-to-face meeting by a multidisciplinary task force panel of experts, including two patient research partners. The level of agreement among the panel in regard to each PtC was established by anonymous online voting. Results: Three overarching principles and 10 PtC were formulated. Three PtC are related to patient safety, considered as a critical issue by the panel. Three are related to relevance of the content and functionalities. The requirement for transparency around app development and funding sources, along with involvement of relevant health professionals, were also raised. Ease of app access across ages and abilities was highlighted, in addition to considering the cost benefit of apps from the outset. The level of agreement was from 8.8 to 9.9 out of 10. Conclusion: These EULAR PtC provide guidance on important aspects that should be considered for the development, evaluation and implementation of existing and new apps.